Causes of Mortality of Northern Sea Otters (Enhydra lutris kenyoni) in Alaska From 2002 to 2012 - Burek Huntington, Kathleen Ann; Gill, Verena Ann; Berrian, Amanda M.; Goldstein, Tracey; Tuomi, Pam; Byrne, Barbara A.; Worman, Kristin; Mazet, Jonna (Frontiers in Marine Science, 2021)
Most of the world’s sea otters reside in Alaska, but there has never been an assessment of long-term mortality patterns for this keystone predator. We examined data collected from 780 northern sea otter (Enhydra lutris kenyoni) carcasses recovered in Alaska from 2002 to 2012 to evaluate the causes of mortality and risk factors associated with death. A smaller group (n = 144, 18%) of fresh non-frozen carcasses were included in a more detailed mortality analysis. Forty-four% of the fresh dead otters were determined to have died from infectious endocarditis, meningoencephalitis, and/or septicemia due to systemic streptococcosis (“Strep syndrome”). Streptococcus lutetiensis, a member of the Streptococcus bovis/equinus (SB/E) group was most commonly isolated, although other members of the SB/E group were identified. There were fewer cases where S. phocae and other streptococci were isolated. A regression analysis revealed age and location risk factors for Strep syndrome. Subadults were the highest risk age group, and otters recovered from the Kachemak Bay region were 3.6 times (95% CI: 2.2–5.9) more likely to die from Strep syndrome than otters recovered elsewhere. Diagnosis of this Strep syndrome had not been reported in other marine mammals in Alaska. Sporadic cases of septicemia and infectious endocarditis due to S. lutetiensis have been seen in the southern sea otter population in California. Other causes of death for the fresh otters included neurologic diseases (10%), trauma (8%), nutritional diseases (7%), cardiovascular diseases (7%), gastrointestinal diseases /parasites (6%), undetermined (5%), septicemia (3%), and neoplasia (3%). All other causes of death (oiling, hepatobiliary, fungal, marine biotoxins, pulmonary) were at or below 1%. Twenty percent of fresh animals were positive for phocine distemper virus (PDV) by polymerase chain reaction (PCR, 11/55), 18% seropositive for PDV (7/38), and paramyxovirus-like particles were demonstrated by electron microscopy within inclusion bodies from one animal. Low concentrations of the harmful algal bloom toxins domoic acid and saxitoxin were also detected in 26% and 22% of fresh animals, respectively. Protozoal disease was rare. These patterns of disease differ from sea otters in other regions and possible reasons are discussed.